Association of MHC antigens with susceptibility to and severity of rheumatoid arthritis in multicase families. Issue 8 (August 1985) - Walker, D J; Griffiths, M; Dewar, P; Coates, E; Dick, W C; Thompson, M; Griffiths, I D
Abstract : A study of HLA association with rheumatoid arthritis (RA) in multicase families has been performed in north east England. Two hundred and nineteen individuals from 13 families were assessed for the presence of RA, and all were HLA typed. Thirty-nine were found to have classical or definite RA by American Rheumatism Association (ARA) criteria. Thirty-five (90%) of these possess HLA-DR4, confirming the previously reported association of RA with DR4. A further 19 individuals were found to have probable RA or gave a convincing history of previous inflammatory polyarthritis. Thirteen (68%) of these possess HLA-DR4, and this is not significantly different from non-affected family members of whom 63% possess DR4. These results suggest that HLA-DR4 is associated only with the more severe forms of RA. Homozygosity for HLA-DR4 was not associated with either earlier onset or more severe disease when compared with heterozygous DR4. Possession of the haplotype most commonly inherited with the RA in individual families was not associated with earlier onset but may be associated with more severe disease. The severity of RA appears to be influenced by the major histocompatibility complex (MHC) in these families.